Factors Influencing Passenger Stress in Low-Cost Airline - คำชื่น ชัยพันธุ์; อาดัม นัสรียา; ทิพยโท ศิรภัสสร; วงศ์มะโน ศิริอักษร (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aims to examine the stress among passengers using low-cost airline services and to analyze service-related factors influencing such stress. A quantitative research approach was employed, using a questionnaire as the primary data collection instrument. Data were collected from passengers who had used low-cost airline services. The independent variables examined included the check-in process and waiting time, clarity of information and communication, additional restrictions and fees, as well as the in-flight environment and travel comfort. The dependent variable was passenger stress, measured through feelings of anxiety, tension, and discomfort experienced during different stages of air travel. The findings of this study are expected to provide a systematic understanding of factors contributing to passenger stress in low-cost airlines and to serve as useful information for improving service processes, communication strategies, and passenger experience management in order to reduce stress and enhance the overall quality of air travel.